2017
DOI: 10.1016/j.jcrs.2017.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular lens power calculation for eyes with high and low average keratometry readings: Comparison between various formulas

Abstract: Power calculation for eyes with flat corneas and steep corneas requires the use of specific formulas for accurate postoperative results. An adjustment method of the SRK/T formula is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 15 publications
3
31
0
2
Order By: Relevance
“…In eyes with normal ALs and high AL/CR ratios, the SRK/ T formula had a strong tendency toward myopic results. Reitblat and colleagues 53 reported that the IOL power calculations for eyes with steep corneas yielded myopic prediction errors with the SRK/T formula. Melles and colleagues 54 reported that the SRK/T formula tended to overestimate the IOL power in eyes with steep corneas.…”
Section: Accuracy Of Iol Power Calculations Accordingmentioning
confidence: 99%
“…In eyes with normal ALs and high AL/CR ratios, the SRK/ T formula had a strong tendency toward myopic results. Reitblat and colleagues 53 reported that the IOL power calculations for eyes with steep corneas yielded myopic prediction errors with the SRK/T formula. Melles and colleagues 54 reported that the SRK/T formula tended to overestimate the IOL power in eyes with steep corneas.…”
Section: Accuracy Of Iol Power Calculations Accordingmentioning
confidence: 99%
“…Faramarzi et al [9] demonstrated that the prediction error was −0.06 ± 0.52 D in eyes with a keratometry >46 D using the SRK/T formula, but that the sample size was limited (n � 45). Reitblat et al [10] showed that myopic refractive errors (−0.31 ± 0.54 D) were found in eyes with a keratometry >46 D, but hyperopic errors (0.16 ± 0.31 D) were noted in eyes with a keratometry <42 D, when the SRK/T formula was used, and that the prediction error was −0.04 ± 0.45 D and −0.07 ± 0.26 D, in eyes with a keratometry >46 D and <42 D, respectively, both of which were not significantly different from zero, when the Barrett Universal II formula was used. eir previous findings are in accordance with our current findings in terms of the prediction error.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, there have only been a few studies on the predictability of the IOL power calculation using the two major formulas, according to the keratometric readings [8][9][10]. Moreover, the detailed relationship between the predictability outcomes and the keratometry has so far not been elucidated using the two major formulas.…”
Section: Introductionmentioning
confidence: 99%
“…The Haigis formula incorporates the AL into the calculation; however, it is noted in clinical practice that small errors in postoperative refractive spherical equivalent still exist. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%